The lived experience of chronic pain and dyskinesia in children and adolescents with cerebral palsy - Clare T. McKinnon; Jennifer H. White; Prue E. Morgan; Giuliana C. Antolovich; Catherine H. Clancy; Michael C. Fahey; Adrienne R. Harvey (BMC, 2020)
Abstract Background To explore the lived experience of chronic pain and dyskinesia in children and adolescents with cerebral palsy. Methods A convergent parallel mixed methods design was undertaken. First, a quantitative cross-sectional study of participants able to self-report their quality of life was undertaken. This study characterised pain chronicity, intensity, body locations, and quality of life. Second, semi-structured interviews were undertaken with a subset of children and adolescents experiencing chronic pain. Results Twenty-five children and adolescents took part in the cross-sectional study, 23 of whom experienced chronic pain and 13 of moderate intensity. Pain was often located in multiple bodily regions (6/21), with no trends in quality of life outcomes detected. Eight participated in semi-structured interviews, which identified three key themes including 'lives embedded with dyskinesia', 'real world challenges of chronic pain', and 'still learning strategies to manage their pain and dyskinesia'. Conclusions A high proportion of children and adolescents with cerebral palsy and dyskinesia who were able to self-report experienced chronic pain. The physical and emotional impacts of living with chronic pain and dyskinesia existed along a spectrum, from those with lesser to greater extent of their impacts. Children and adolescents may benefit from targeted chronic pain education and management within bio-psychosocial models.